Pod jednym dachem ze smokiem. Biblioterapeutyczna lektura książki obrazkowej Dragen Gro Dahle i Sveina Nyhusa (Heteroglossia – studia kulturoznawczo-filologiczne, 2025)
The article examines the therapeutic aspect of the picturebook Dragen (2018) by the popular Norwegian artistic duo Gro Dahle and Svein Nyhus. By applying selected elements of multimodal analysis and the concept of mindscape, the analysis reveals how meanings with a strong interpersonal function are generated. These meanings create a poignant iconotextual depiction of the inner world of a child facing an abusive mother. The picturebook highlights the necessity for the child to escape the oppressive, isolated environment and seek help. To address this challenging topic, the artists employ a metaphorical verbal and visual language based on the symbolism of the dragon.